Development Of Sustainable Business Models For Community-Based Smes In Medan: An Islamic Economic Perspective - Pranata, Mhd Harry; Syahbudi, Muhammad; Nasution, Juliana (UNIVERSITAS PAKUAN, 2017)
This article attempts to develop a sustainable business model for community-based Micro, Small, and Medium Enterprises (MSMEs) in Medan City from the perspective of Islamic economics. This initiative is driven by the fact that there are currently 38,343 MSMEs registered in the Cooperative and MSME Data System (SIMDAKOP) application of Medan City, which must be able to endure. The methodology used is a qualitative approach, with data collection through interviews and surveys completed by participants, analyzed using a SWOT analysis based on the triple bottom line. The results of this study indicate that the sustainable business model for community-based MSMEs in Medan City, approached through SWOT analysis, is a competitive strategy achieved through ST (Strengths and Threats) collaboration. The program planning includes: (1) enhancing MSME collaboration with government institutions and academics to improve MSME competitiveness; (2) increasing environmentally friendly and locally sourced product innovation; and (3) improving funding sources from CSR programs of institutions or state-owned enterprises (SOEs) to support MSMEs, ensuring that their products and prices remain affordable despite economic instability. The contribution of this article is the proposal of a sustainable business model that is expected to withstand the challenges posed by all the core issues previously mentioned in the context of Islamic economics. Keywords: This article attempts to develop a sustainable business model for community-based Micro, Small, and Medium Enterprises (MSMEs) in Medan City from the perspective of Islamic economics. This initiative is driven by the fact that there are currently 38,343 MSMEs registered in the Cooperative and MSME Data System (SIMDAKOP) application of Medan City, which must be able to endure. The methodology used is a qualitative approach, with data collection through interviews and surveys completed by participants, analyzed using a SWOT analysis based on the triple bottom line. The results of this study indicate that the sustainable business model for community-based MSMEs in Medan City, approached through SWOT analysis, is a competitive strategy achieved through ST (Strengths and Threats) collaboration. The program planning includes: (1) enhancing MSME collaboration with government institutions and academics to improve MSME competitiveness; (2) increasing environmentally friendly and locally sourced product innovation; and (3) improving funding sources from CSR programs of institutions or state-owned enterprises (SOEs) to support MSMEs, ensuring that their products and prices remain affordable despite economic instability. The contribution of this article is the proposal of a sustainable business model that is expected to withstand the challenges posed by all the core issues previously mentioned in the context of Islamic economics. Keywords: Model, Sustainable Business, MSMEs, SWOT, TBL